Services marketing : integrating customer focus across the firm - Zeithaml, Valarie A.; Bitner, Mary Jo; Gremler, Dwayne D. (McGraw-Hill Education, 2018)
"This text is for students and business people who recognize the vital role that services play in the economy and its future. The advanced economies of the world are now dominated by services, and virtually all companies view service as critical to retaining their customers today and in the future. Manufacturing and product-dominant companies that, in the past, have depended on their physical products for their livelihood now recognize that service provides one of their few sustainable competitive advantages"-- Provided by publisher
Revised edition of the authors' Services marketing, c2013
Keywords: BUSINESS & ECONOMICS -- Marketing -- Multilevel; Customer services; Marketing; Service industries -- Marketing